2005
DOI: 10.1242/jeb.01588
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and power-laws in ecological systems

Abstract: Scaling relationships (where body size features as the independent variable) and power-law distributions are commonly reported in ecological systems. In this review we analyze scaling relationships related to energy acquisition and transformation and power-laws related to fluctuations in numbers. Our aim is to show how individual level attributes can help to explain and predict patterns at the level of populations that can propagate at upper levels of organization. We review similar relationships also appearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
315
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(323 citation statements)
references
References 256 publications
7
315
0
1
Order By: Relevance
“…These relationships were a spatial TL (spatial variance in population density was a power-law function of the spatial mean population density); DMA (the spatial mean population density was a power-law function of mean body mass); and VMA (the spatial variance in population density was a power-law function of mean body mass). Third, TL and DMA, both classic relationships known for decades, accurately predicted the form and parameter values of VMA, a power-law relationship predicted only within the last decade (8,9,23), and previously tested empirically only once (9). To our knowledge, we provided here the first empirical confirmation of VMA for any animal community.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These relationships were a spatial TL (spatial variance in population density was a power-law function of the spatial mean population density); DMA (the spatial mean population density was a power-law function of mean body mass); and VMA (the spatial variance in population density was a power-law function of mean body mass). Third, TL and DMA, both classic relationships known for decades, accurately predicted the form and parameter values of VMA, a power-law relationship predicted only within the last decade (8,9,23), and previously tested empirically only once (9). To our knowledge, we provided here the first empirical confirmation of VMA for any animal community.…”
Section: Discussionsupporting
confidence: 61%
“…Marquet et al (8) and Cohen et al (9) independently showed theoretically that TL and DMA combine to predict the form and parameters of an allometric relationship between the variance of population density and mean body mass (variance-mass allometry, or VMA). (The details of these predictions are in SI Appendix.)…”
Section: Significancementioning
confidence: 99%
“…The relationship between phytoplankton abundance and cell size in aquatic ecosystems follows a power function, N ¼ a V b , where N is the cell density and a is the intercept of the resulting linear regression. The size-scaling exponent, b, is a synthetic descriptor of community size structure [2] and generally takes values between 21.3 and 20.6. The value of the size-scaling exponent is strongly related to ecosystem's productivity.…”
Section: Introductionmentioning
confidence: 99%
“…A striking feature of complex systems is that they show regularities in the behavior of macroscopic variables, which emerge as the result of nonlinear interactions among multiple components and because of the competition of opposing control forces (4-6). These regularities commonly take the form of simple scaling relationships or power-laws (7,8). A macroscopic variable that shows scaling relationships is metabolic rate (VO 2 ) (the rate at which an animal consumes oxygen), which scales with body mass (M) such that VO 2 ϰ M a with ␣Ͻ1.…”
mentioning
confidence: 99%